The relation between lateral thinking and inquiry skills of higher education students: A path analysis - Duman, Burcu; Yılmaz, Emrullah; Tural, Aysegul; Şahan, Gülsün; Şahan, Gülsün; Yılmaz, Emrullah; Duman, Burcu; Tural, Ayşegül (Wiley, 2024)
The aim of the study is to examine the relations between higher education students' lateral thinking dispositions and inquiry skills. Survey design and Structural Equation Modelling were used in the study. The sampling of the study consisted of 975 prospective teachers attending three faculties of education in three different state universities in Turkey. Inquiry Skills Scale and Lateral Thinking Disposition Scale were used to collect data. The collected data were analysed using R Studio programme. It was observed in the study that students' inquiry skills and lateral thinking dispositions were high. It was revealed in the study that inquiry skills predicted lateral thinking dispositions. Inquiry skills account for 31% of lateral thinking disposition. Thus, it can be concluded that lateral thinking dispositions of higher education students' depend on their inquiry skills at a percentage of 31%.
Keywords: Higher Education; Inquiry; Path Analysis; Relation; Thinking